Production of Bio-Fertilizer through Composting of Tannery Wastes with Cow- Dung and Rice Bran - Lambu, Z.N.,; Shamsuddeen, U.; Yahaya, S.; Aliyu, A.S.; Karfi, A.I.; Isyaku, J.,; Mahmud, T.; Y. S. Mohammed (UMYU Journal of Microbiology Research)
Tannery waste is made from nutrients and organic compounds that enhance soil fertility thereby improving plants and microbial growths. This study was designed to investigate the application of tannery wastes to form compost material in a mixture with cow-dung and rice brand. The treatments were prepared and tested for a period of sixty (60) days. The compost was characterized by electric conductivity (EC) of 10.11µs/cm, pH of 7.62 and Carbon-Nitrogen (C:N) ratio of 28.8. Total concentrations of Chromium, Lead, Cadmium, Copper, Zinc and Iron in mg/kg were 57.2, 0.92, 12.50, 60.50, 13.60 and 1101.00 respectively. However, total bacterial counts decreased from 8.2 x108cfu/g to 1.8 x106cfu/g after the 60days. The compost characteristics indicate about 80% germination index which may suggest the removal of most of the phototoxic compounds.